Novel temperature-stable (1-x)Ba3V2P3O15-xBaV2O6 composite ceramics with ultralow sintering temperature and low dielectric loss for dielectric resonator antenna applications - Wang, Chang Hao; Zhang, Kai Heng; Bao, Jian; Jiang, Jia Pei; Xu, Di Ming; Du, Chao; Pang, Li Xia; Zhou, Tao; Tan, Kar Ban; Zhou, Di (John Wiley and Sons I, 2025)
The phase composition, crystal structures, dielectric properties, and thermal characteristics of novel (1-x)Ba3V2P3O15-xBaV2O6 (0 ≤ x ≤ 1) composite ceramics are systematically investigated. The composite ceramics are rationally designed by combining novel Ba3V2P3O15 ceramics with BaV2O6 ceramics, enabling the regulation of microwave dielectric properties. Experimental results demonstrate that pure-phase Ba3V2P3O15 ceramics sintered at 720 °C for 2 h exhibit outstanding microwave dielectric properties: permittivity (εr) = 7.5, quality factor (Q×f) = 25 920 GHz (at 12.22 GHz), and temperature coefficient of resonant frequency (τf) = −38 ppm °C−1. Notably, 0.2Ba3V2P3O15-0.8BaV2O6 ceramics sintered at 580 °C for 2 h achieve excellent microwave dielectric properties: εr = 10.0, Q×f = 21 600 GHz (at 10.92 GHz), and τf = +3.5 ppm °C−1. Additionally, 0.2Ba3V2P3O15-0.8BaV2O6 ceramics exhibit superior terahertz dielectric performance, highlighting significant potential for terahertz applications. Furthermore, 0.2Ba3V2P3O15-0.8BaV2O6 ceramics show favorable compatibility with Al electrodes, demonstrating significant potential for ultralow temperature co-fired ceramic (ULTCC) application. A cylindrical dielectric resonator antenna (DRA) element is designed using 0.2Ba3V2P3O15-0.8BaV2O6 ceramics, exhibiting a high radiation efficiency of 88.7% and a peak realized gain of 5.56 dBi. Both simulated and measured performances of the DRA are exceptional, indicating its promising applicability in 5.8 GHz Wi-Fi communication systems.